ANALYSIS OF NATURALLY OCCURRING PENOLIC COMPOUNDS OF THE GENERA CLINOPODIUM L. , HYMENOCRATER FISH & C. A. MEY. AND MELISSA L. - & et al., AL-Zubaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Six taxa of Lamiaceae family including three taxa of the genus Clinopodium L. (C. vulgare subsp. vulgareL., C. umbrosum (M. B.) C. Koch. and C. congstum Boiss. & Hausskn ex. Boiss. ) and two of the genus Hymenocrater Fish. & C. A. Mey. (H,longiflora Benth. H. bituminosus Fish & C. A. Mey) and one of the genus Melissa (M.officinalis subsp.fficinalis L.) were studied in order to evaluate their phenolic profile ,as these taxa were studied in such detail for the first time in Kurdistan region of Iraq . The examined phenolic substances which studied in these taxa include: Caffeine, Coumarin, Eugenol Estragole(4- Allyl anisole), 2-6 Dimethyl phenol, Salicylic acid and P-Cresol, by using high performance liquid chromatography (HPLC) technique. The results showed that the most abundant phenolic compound were: Caffeine and 2-6Dimethyl phenol which found in all the studied taxa, followed by Eugenol and Salicylic acid which found in five of the six studied taxa, whereas the less prevalent phenolic compounds were )Coumarin and Estragole(4- Allyl anisole),which found in just two of the studied taxa. The deference in distribution of the phenolic compound in the studied taxa can be utilized to differentiate between them in studies of genetic diversity and chemotaxonomy as it can be possible to distinguish between the genera Clinopodium, Hymenocrater and Melissa beside the distinguish between the taxa of the same genus ( Clinopodium ), using phenolic profile.